Whole-Transcriptome Sequencing-Based Profiling of the Cutaneous Virome in Patients with Secondary Immunodeficiency - Leila Youssefian; Amir Hossein Saeidian; Zahra Saffarian; Mona Ariamanesh; Fahimeh Abdollahimajd; Sara Molkara; Mohammad Shahidi-Dadras; Reem Diab; Fatemeh Vahidnezhad; Sirous Zeinali; Vivien Béziat; Emmanuelle Jouanguy; et al. (Elsevier, 2024)
Most viral infections can be self-limited, with no requirement for medical intervention. However, the same viruses can cause severe diseases in patients with compromised immunity due to single-gene diseases, acquired immune deficiency syndrome, or hematologic malignancies or those receiving immunosuppressive drugs. Occasionally, these immunocompromised patients harbor >1 infectious agent, requiring several concomitant diagnostic tests. We have developed, to our knowledge, a previously unreported whole-transcriptome sequencing-based pipeline that allows virome profiling, quantitation, and expression pattern analysis of 926 distinct viruses by sequencing of RNA isolated from a single lesional skin biopsy. This pipeline can also explore host genetics if there is a Mendelian predisposition to infection. We applied this pipeline to 6 Iranian patients with viral-induced skin lesions associated with immune deficiency secondary to HIV, human T-lymphotropic virus 1, chronic lymphocytic leukemia, and post transplant immunosuppression. In 5 cases, definitive human papillomavirus infections were identified, some caused by multiple viral types. In addition to human papillomavirus, coinfection with other viruses (Merkle cell polyomavirus, cytomegalovirus, and human herpesvirus 4) was detected in some lesions. In 1 case, whole-transcriptome sequencing validated the clinical diagnosis of adult T-cell leukemia/lymphoma in a patient with an initial diagnosis of mycosis fungoides/Sézary syndrome. These findings attest to the power of whole-transcriptome sequencing in profiling the cutaneous virome in the context of compromised immunity.